تأصيل الأنا الوجودية في ظل الشيزوفينيا الأنثروبولوجية - بالشيخ, أسماء (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
يحاول هذا المقال الاجابة عن مدىواقعيةايجادهويةمحلية لعلما لأنتروبولوجيا،وماواقعهالآنيفيظلالمعطياتالميدانيةوالأكاديميةوالاستشرافية،وكيف يمكن التخلص منهاتهالشيزوفينياالمنحلفيهاعمليا واجرائيا. This article tries to answer the reality of finding a local identity of the science of anthropology and whatispresent in the light of the field, academic and future data, and how to getrid of theseschizophreniacharacterized by anthropologypractically and procedurally.